Konsep Kebahagiaan (Sa'adah) dalam Filsafat Islam: Telaah Terhadap Pemikiran Ibnu Miskawaih - Siti Khalishah Ramadhani (Al-Widad, 2024)
This study aims to analyze the concept of happiness (sa‘ādah) in Islamic philosophy according to Ibn Miskawayh and to examine its relevance in modern life. The study employs a qualitative approach using a library research method, relying on the analysis of Ibn Miskawayh’s works and various relevant scholarly sources. The data were analyzed through content analysis to identify and interpret the main ideas concerning happiness in his philosophical thought. The findings reveal that sa‘ādah, according to Ibn Miskawayh, is a state of spiritual perfection attained through the cultivation of reason, the development of virtuous character, and the control of human desires. Happiness is not merely oriented toward material aspects but also encompasses moral and spiritual dimensions that lead individuals toward the perfection of life. This concept remains relevant in addressing the tendency of modern society to define happiness in materialistic and individualistic terms.